2019
DOI: 10.1002/aenm.201901896
|View full text |Cite
|
Sign up to set email alerts
|

Sulfiphilic Few‐Layered MoSe2 Nanoflakes Decorated rGO as a Highly Efficient Sulfur Host for Lithium‐Sulfur Batteries

Abstract: Lithium‐sulfur batteries (LSBs) have been regarded as a competitive candidate for next‐generation electrochemical energy‐storage technologies due to their merits in energy density. The sluggish redox kinetics of the electrochemistry and the high solubility of polysulfides during cycling result in insufficient sulfur utilization, severe polarization, and poor cyclic stability. Herein, sulfiphilic few‐layered MoSe2 nanoflakes decorated rGO (MoSe2@rGO) hybrid has been synthesized through a facile hydrothermal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 64 publications
(114 reference statements)
2
115
0
Order By: Relevance
“…The spectra are consisted of a semicircle at the high‐ to medium‐frequency region and an inclined straight line at the low‐frequency region. According to previous literature, the semicircle belongs to the resistance of SEI film ( R SEI ) and the charge‐transfer resistance ( R ct ), [43,44,45] and the straight line can be assigned to the lithium ion diffusion in electrodes, known as the Warburg impedance ( Z w ) [46,47,48] . As shown in Figure 6a, in comparison to Si@C anodes, the Si@C−Co 9 S 8 /C anodes show the relative lower R ct , suggesting high electrical conductivity of the Si@C−Co 9 S 8 /C anodes.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The spectra are consisted of a semicircle at the high‐ to medium‐frequency region and an inclined straight line at the low‐frequency region. According to previous literature, the semicircle belongs to the resistance of SEI film ( R SEI ) and the charge‐transfer resistance ( R ct ), [43,44,45] and the straight line can be assigned to the lithium ion diffusion in electrodes, known as the Warburg impedance ( Z w ) [46,47,48] . As shown in Figure 6a, in comparison to Si@C anodes, the Si@C−Co 9 S 8 /C anodes show the relative lower R ct , suggesting high electrical conductivity of the Si@C−Co 9 S 8 /C anodes.…”
Section: Resultsmentioning
confidence: 71%
“…According to previous literature, the semicircle belongs to the resistance of SEI film (R SEI ) and the charge-transfer resistance (R ct ), [43,44,45] and the straight line can be assigned to the lithium ion diffusion in electrodes, known as the Warburg impedance (Z w ). [46,47,48] As shown in Figure 6a, in comparison to Si@C anodes, the Si@CÀ Co 9 S 8 /C anodes show the relative lower R ct , suggesting high electrical conductivity of the Si@CÀ Co 9 S 8 /C anodes. Therefore, Si@CÀ Co 9 S 8 /C anodes display dramatically enhanced electrochemical performance, which can be ascribed to the rational structural design of Si@CÀ Co 9 S 8 /C.…”
Section: Lithium Storage Performance Characterizationmentioning
confidence: 97%
“…[ 88 ] For example, our group demonstrated that MoSe 2 @rGO can provide faster LiPSs conversion kinetics than rGO by comparing their i 0 values calculated from Tafel plots ( Figure 7 a). [ 89 ]…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…Transition metal selenides with moderate electronegativity differences between transition metals and selenium as well as the variable oxidation state of selenium possess superior catalytic effect and therefore attract tremendous attention for energy storage (such as sodium‐ion battery anodes, solar cells, photocatalysis, and HER process) in recent years. In addition, compared with sulfides, selenides exhibit higher conductivity (1 × 10 −3 S m −1 vs 5 × 10 −28 S m −1 ) which was usually employed to form selenium–sulfur solid solutions for compensating the inferior conductivity and stiff activity of S. [ 89,122 ] Despite these merits, the researches of metal selenides in the Li–S systems especially served as catalytic materials is still at its early stage.…”
Section: Emerging Metal‐based Catalytic Materials For Li–s Batteriesmentioning
confidence: 99%
“…All these features suggest the metal selenides could be good candidates to enhance the performances of S cathode by mitigate the polysulfides shuttle effect by chemically adsorb the polysulfides and catalytic acceleration of redox kinetics. Recently, several creative studies were reported for the successful applications of metal selenides' in Li-S batteries [34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%